2020
DOI: 10.1128/iai.00503-20
|View full text |Cite
|
Sign up to set email alerts
|

The Arg753Gln Polymorphism of Toll-Like Receptor 2 Has a Lower Occurrence in Patients with Syphilis, Suggesting Its Protective Effect in Czech and Slovak Individuals

Abstract: Syphilis is a bacterial infection caused by Treponema pallidum subsp. pallidum (TPA). Infection and dissemination of TPA leads to synthesis of proinflammatory cytokines triggered by TPA lipoproteins interacting with Toll-like receptor 2 (TLR2). TLR2 contains several non-synonymous single-nucleotide polymorphisms that may impact the activation of its signaling cascade and alter the responsiveness to, or course of, various infectious diseases; including those caused by pathogenic spirochetes. To investigate whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 28 publications
0
7
5
Order By: Relevance
“…While the previous work (Grillová et al (2020) [18]) on the Czech and Slovak populations identified the TLR2 Arg753Gln polymorphism as a possible protective factor against syphilis, our current study did not find this association. Nevertheless, a similar, but not statistically significant, trend was noticed in this study, where the control group had a higher prevalence of Arg753Gln heterozygotes (GA, Table 1) compared to the syphilis-positive participants.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…While the previous work (Grillová et al (2020) [18]) on the Czech and Slovak populations identified the TLR2 Arg753Gln polymorphism as a possible protective factor against syphilis, our current study did not find this association. Nevertheless, a similar, but not statistically significant, trend was noticed in this study, where the control group had a higher prevalence of Arg753Gln heterozygotes (GA, Table 1) compared to the syphilis-positive participants.…”
Section: Discussioncontrasting
confidence: 97%
“…Despite an overall 3% frequency, its distribution differs greatly among various European populations. The highest frequency was found in the Czech and Slovak populations [18] and among a Turkish population [19], both around 10%. On the other hand, in southern Europe, this SNP has a low frequency [20].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The patients may also have genetic susceptibilities to STIs. Indeed there might be an association between genetic variants in host protein disulfide isomerase 2 and susceptibility to Chlamydia infection, between polymorphism in Toll-like receptor 2 and syphilis, and between susceptibility to Neisseria gonorrhoeae and human leukocyte antigen alleles and IL-2 polymorphism [20–22].…”
Section: Discussionmentioning
confidence: 99%
“…In syphilis patients, the Arg753Gln change had a much lower frequency than in controls. The findings implied that Arg753Gln ( TLR2 ) does protect against syphilis development ( 16 ).…”
Section: Host Factors Associated With Sexually Transmitted Infectionsmentioning
confidence: 99%